2015
DOI: 10.1002/jor.22812
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral heat accelerates bone elongation and lengthens extremities of growing mice

Abstract: Linear growth failure results from a broad spectrum of systemic and local disorders that can generate chronic musculoskeletal disability. Current bone lengthening protocols involve invasive surgeries or drug regimens, which are only partially effective. Exposure to warm ambient temperature during growth increases limb length, suggesting that targeted heat could noninvasively enhance bone elongation. We tested the hypothesis that daily heat exposure on one side of the body unilaterally increases femoral and tib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Alternatively, recent research (Holton et al, ) has suggested that nasal components of the chondrocranium, including the turbinates, may influence the development of surrounding intramembranous‐derived nasal structures (e.g., maxillae, premaxillae, nasal bones) during ontogeny. Experimental studies (Serrat, ; Serrat et al, ; Serrat, King, & Lovejoy, ; Serrat, Williams, & Farnum, ) have concurrently demonstrated that environmental temperatures can directly alter cartilage development (and ultimately endochondral bone morphology) via effects on cell proliferation and matrix production. It thus appears conceivable that the temperature of environmental air entering the nasal passages during early postnatal life could potentially impact inferior turbinate morphology via influence on any remaining cartilaginous components.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, recent research (Holton et al, ) has suggested that nasal components of the chondrocranium, including the turbinates, may influence the development of surrounding intramembranous‐derived nasal structures (e.g., maxillae, premaxillae, nasal bones) during ontogeny. Experimental studies (Serrat, ; Serrat et al, ; Serrat, King, & Lovejoy, ; Serrat, Williams, & Farnum, ) have concurrently demonstrated that environmental temperatures can directly alter cartilage development (and ultimately endochondral bone morphology) via effects on cell proliferation and matrix production. It thus appears conceivable that the temperature of environmental air entering the nasal passages during early postnatal life could potentially impact inferior turbinate morphology via influence on any remaining cartilaginous components.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Serrat, King, and Lovejoy () and Serrat () found that mice housed at 7 °C had shorter bodies, tails, and limb bones than mice raised at 27 °C, despite higher food intake and no difference in body mass. Importantly, cold exposure reduced blood flow and solute transport to limb bone growth plates in vivo (Serrat et al, ; Serrat, Williams, & Farnum, ), whereas cold‐induced reductions in growth were mitigated by exercise (Serrat, Williams, & Farnum, ) and hindlimb heating (Serrat, ; Serrat et al, ). These studies strongly suggest circulation to the growth plate underlies temperature‐induced differences in limb length, and reduced circulation may contribute to the decreased trabecular bone architecture we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Premature, unilateral closure and smaller hips may lead to altered gait and degenerative outcomes . Conversely, asymmetric growth plate expansion of murine long bones of the hindlimb has been shown to be modulated by the delivery of heat, which led to limb length discrepancy and the potential for altered loading patterns between left and right hips . Adaptations to loading during postnatal growth may influence proliferation and differentiation of growth plate cells, particularly of the triradiate cartilage and proximal femur, and future work should explore this further.…”
Section: Discussionmentioning
confidence: 99%